EMPOWERMENT OF THE DIRECTORATE OF ARMY FINANCE AND THE ARMY COMPULSORY HOUSING SAVINGS MANAGEMENT AGENCY AS PILLARS OF SOLDIER WELFARE: Pemberdayaan Direktorat Keuangan Angkatan Darat dan Badan Pengelola Tabungan Wajib Perumahan Angkatan Darat Guna Mendukung Kesejahteraan Prajurit - Muslimin Fahsyah; Mhd Halkis; Rachmat Indra Kurniawan Gani Rachmat (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to explain the role of empowering the Directorate of Army Finance and the Army Compulsory Housing Savings Management Agency in achieving soldier welfare to support national development. One indicator of soldier welfare is the fulfillment of housing needs, which aligns with national development goals. As integral organizations of the Indonesian Army, the Directorate of Army Finance and the Army Compulsory Housing Savings Management Agency are mandated to manage and optimize Compulsory Housing Savings and Home Ownership Loans for soldiers. This study uses a qualitative method with a descriptive analysis approach. Primary data were collected through observations and interviews with key informants, while secondary data were gathered from relevant documentation and archives. Data collection techniques included observations, interviews, documentation, and literature review. Qualitative data analysis was performed through descriptive presentation to draw conclusions about the studied phenomena. The research subjects include the Chief of Army Staff, Chief of Army Personnel Staff, Director of Army Finance, and Head of the Army Compulsory Housing Savings Management Agency.The results indicate that empowering the Directorate of Army Finance and the Army Compulsory Housing Savings Management Agency plays a significant role in overcoming obstacles and providing alternative solutions in managing Home Ownership Loans through collaboration with banks and developers, making this empowerment an integral part of national development undertaken by the Indonesian Army. Future opportunities include efforts to develop independent management of Compulsory Housing Savings and Home Ownership Loans, including establishing an internal financial institution. This empowerment is expected to strengthen soldier welfare through personal home ownership, in alignment with national development goals.